The Morphological Impact of the Colibița Hydrotehnical System on the Bistrita Ardeleana Riverbed - Aurelian Cosmin MOLDOVAN; Raul SILAGHI (Aerul şi Apa: Componente ale Mediului, 2021)
Large dams, as well as conventional hydrotechnical constructions with the role of breaking the drainage slope (waterfalls or bottom sills), flood mitigation or with the role of protection against floods (shore defences) have a profound impact on the environment. Due to these constructions, the ecosystems on the Bistrița Ardeleană river have undergone changes or even established new ones. This paper wants to highlight the morphological changes of the Bistriţa riverbed by analysing the transversal profiles made between 1972 and 2015. The profiles were made in the flow measurement section at two hydrometric stations, one being located in the upstream part of the river basin and the other before the Bistrița river flows into the Șieu river. By comparing the results obtained from the profiles made before the Colibița hydrotechnical system was started or completed with the data obtained from the profiles after the commissioning of the Colibița hydropower plant, we managed to highlight that the Bistrița Ardeleană riverbed registered several negative effects in terms of morphologically both vertically and horizontally. We also found that the riverbed downstream of the dam there is a phenomenon called hydraulic paving.